PERILAKU PENATAAN DAN PENGELOLAAN RUANG TERBUKA HIJAU DI KOTA PONTIANAK - Roma Filani E.01107102 (FISIP Universitas Tanjungpura, 2013)
Regarding the administration and management of green space in the city of Pontianak related to the behavior ofstakeholders in the implementation. This study used qualitative methods and do descriptively in depth, as wellas the methods used to help the research is done by observation, interview guides and documentation. Theresults of this study found that there has not been any active role among the stakeholders in the city to realize thepresence of green space, which according to the Spatial Planning Act 26 of 2007 that requires the city have anallocation of 30% green space. The absence of legislation Keywords: the behavior of stakeholder, positive participation, implementing of professionalism